Efficacy of Drug-Coated Balloon Approaches for de novo Coronary Artery Diseases: A Bayesian Network Meta-Analysis - Zhong, Peng-Yu; Ma, Ying; Shang, Yao-Sheng; Niu, Ying; Bai, Nan; Wang, Zhi-Lu (Frontiers in Cardiovascular Medicine, 2022)
Background and objective: The de novo coronary lesions are the most common form of coronary artery disease, and stent implantation still is the main therapeutic strategy. This network meta-analysis aims to evaluate the efficacy of drug-coated balloons only (DCB only) and DCB combined with bare-metal stents (DCB+BMS) strategies versus drug-eluting stents (DES) and BMS approaches in coronary artery de novo lesion. Method: PubMed, EMBASE and Cochrane Library databases were retrieved to include the relevant randomized controlled trials that compared DCB approaches and stents implantation in patients with de novo coronary artery diseases. The primary outcome was major adverse cardiac events (MACE). The clinical outcomes included target lesion revascularization (TLR), all-cause death and myocardial infarction. The angiographic outcomes consisted of in-segment late lumen loss (LLL) and binary restenosis. The odds risk (OR) and 95% confidence intervals (CI) for dichotomous data, weighted mean differences for continuous data were calculated in the Bayesian network frame. Result: A total of 26 randomized controlled trials and 4664 patients were included in this study. The DCB only strategy was comparable with the efficacy of MACE, clinical outcomes and binary restenosis compared with DES. In addition, this strategy can significantly reduce the in-segment LLL compared with the first-generation (MD -0.29, -0.49 to -0.12) and the second-generation DES (MD -0.15, -0.27 to -0.026). However, subgroup analysis suggested that DCB only was associated with higher in-segment LLL than DES (MD 0.33, 0.14 to 0.51) in patients with acute coronary syndrome. Compared with DES, the DCB+BMS strategy had a similar incidence of myocardial infarction and all-cause death, but a higher incidence of MACE, TLR and angiographic outcomes. In addition, although DCB+BMS was associated with a similar incidence of myocardial infarction and all-cause death than BMS, with a lower incidence of MACE, TLR and angiographic outcomes. Conclusions: The DCB only is associated with similar efficacy and lower risk of LLL compared with DES. In addition, the DCB+BMS strategy is superior to BMS alone but inferior to DES (PROSPERO, CRD 42021257567).